Effects of the Ankle Flexion Angle During Anterior Talofibular Ligament Reconstruction on Ankle Kinematics, Laxity, and In Situ Forces of the Reconstructed Graft. (May 2022) - Sakakibara, Yuzuru; Teramoto, Atsushi; Takagi, Tetsuya; Yamakawa, Satoshi; Shoji, Hiroaki; Okada, Yohei; Kobayashi, Takuma; Kamiya, Tomoaki; Fujimiya, Mineko; Fujie, Hiromichi; Watanabe, Kota; Yamashita, Toshihiko
Background: This study aimed to evaluate the effects of the ankle flexion angle during anterior talofibular ligament (ATFL) reconstruction on ankle kinematics, laxity, and in situ force of a graft. Methods: Twelve cadaveric ankles were evaluated using a 6–degrees of freedom robotic system to apply passive plantar flexion and dorsiflexion motions and multidirectional loads. A repeated measures experiment was designed using the intact ATFL, transected ATFL, and reconstructed ATFL. During ATFL reconstruction (ATFLR), the graft was fixed at a neutral position (ATFLR 0 degrees), 15 degrees of plantar flexion (ATFLR PF15 degrees), and 30 degrees of plantar flexion (ATFLR PF30 degrees) with a constant initial tension of 10 N. The 3-dimensional path and reconstructed graft tension were simultaneously recorded, and the in situ force of the ATFL and reconstructed grafts were calculated using the principle of superposition. Results: The in situ forces of the reconstructed grafts in ATFLR 0 degrees and ATFLR PF 15 degrees were significantly higher than those of intact ankles. The ankle kinematics and laxity produced by ATFLR PF 30 degrees were not significantly different from those of intact ankles. The in situ force on the ATFL was 19.0 N at 30 degrees of plantar flexion. In situ forces of 41.0, 33.7, and 21.9 N were observed at 30 degrees of plantar flexion in ATFLR 0, 15, and 30 degrees, respectively. Conclusion: ATFL reconstruction with the peroneus longus (PL) tendon was performed with the graft at 30 degrees of plantar flexion resulted in ankle kinematics, laxity, and in situ forces similar to those of intact ankles. ATFL reconstructions performed with the graft fixed at 0 and 15 degrees of the plantar flexion resulted in higher in situ forces on the reconstructed graft. Clinical Relevance: Fixing the ATFL tendon graft at 30 degrees of plantar flexion results in an in situ force closest to that of an intact ankle and avoids the excessive tension on the reconstructed graft.